2012
DOI: 10.1007/s10456-012-9289-6
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor

Abstract: Folate is important for normal cell division. Folate deficiency has been implicated in various diseases, including atherosclerosis, neural tube defects, and cancer. However, the effect of folate on angiogenesis was unclear. The aim of this study was to investigate the anti-angiogenic action of folic acid (FA). FA (0-10 μmol/L) concentration-dependently decreased DNA synthesis and proliferation in cultured human umbilical venous endothelial cells (HUVEC). Western blot analyses demonstrated that the levels of p2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…The addition of folates to cells activates intracellular signaling pathways in a FR-dependent manner in time periods that are shorter than would be expected from changes in one-carbon metabolism. The addition of folic acid to mammalian cells has been reported to induce the phospho-activation of c-src tyrosine kinase, ERK kinase, and STAT transcription factor in a FRα-dependent manner within 2–5 minutes of stimulation (Hansen et al, 2015; Lin et al, 2012; Zhang et al, 2009). Additionally, FRα itself has been reported to translocate to the nucleus and function as a transcription factor in human tissue culture cells after stimulation with 453 μM of folic acid (Boshnjaku et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of folates to cells activates intracellular signaling pathways in a FR-dependent manner in time periods that are shorter than would be expected from changes in one-carbon metabolism. The addition of folic acid to mammalian cells has been reported to induce the phospho-activation of c-src tyrosine kinase, ERK kinase, and STAT transcription factor in a FRα-dependent manner within 2–5 minutes of stimulation (Hansen et al, 2015; Lin et al, 2012; Zhang et al, 2009). Additionally, FRα itself has been reported to translocate to the nucleus and function as a transcription factor in human tissue culture cells after stimulation with 453 μM of folic acid (Boshnjaku et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this mechanism, folic acid binds to its receptor (folic acid receptor) and subsequently activates the extracellular-signal-regulated kinases/NFkB/-signaling pathway which, in turn, upregulates the expression of p21 and p27 and finally results in cell cycle arrest at the G0/G1 phase inhibiting vascular endothelial cell proliferation (160).…”
Section: Proposed Mechanism Of Actionmentioning
confidence: 99%
“…Plasma total homocysteine is associated with an increased risk of coronary artery disease (176). Folic acid is the fully oxidized monoglutamyl form of folate and is frequently used as the nutritional supplement of folate due to its stability and bioavailability (160). Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of eNOS, the enzyme catalyzing the formation of NO, and is a mediator of atherogenic effects of homocysteine.…”
Section: Clinical Trial Evidence and Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results based on the population and in vitro studies showed that levels of RBC folate were decreased with the severity of cervical lesions, proliferation inhibition rate and apoptosis rate gradually increased in CC cells (HPV16 positive or negative) with the increasing folate concentrations. Shyr and colleagues (28) reported folic acid (0-10 µmol/l) concentration-dependently decreased DNA synthesis and proliferation in cultured human umbilical venous endothelial cells (HUVEC). Other research have shown that folic acid can promote dose dependent cell proliferation in folate receptor α (FRα)-positive HeLa cells, but not in FRα-negative HEK293 cells (29).…”
Section: Discussionmentioning
confidence: 99%